Expanded (G/G2) Expansion Method to Solve Separated Variables for the 2+1-Dimensional NNV Equation - Yong Meng (Advances in Mathematical Physics)
The traditional (G/G2) expansion method is modified to extend the symmetric extension to the negative power term in the solution to the positive power term. The general traveling wave solution is extended to a generalized solution that can separate variables. By using this method, the solution to the detached variables of the symmetric extended form of the 2+1-dimensional NNV equation can be solved, also the soliton structure and fractal structure of Dromion can be studied well.